Development of HACCP system for production of natural dry red wine - Usatyuk, Svitlana; Tyshchenko (Usatiuk), Olena; Klymash, Nataliia (My University, 2016)
The development of the HACCP system for the production of natural dry red wine is considered.
Keywords: HACCP; вино червоне сухе; кафедра експертизи харчових продуктів; кафедра готельно-ресторанної справи